Mitochondrial genome and nuclear ribosomal RNA analysis place Alveonasus lahorensis within the Argasinae and suggest that the genus Alveonasus is paraphyletic - Ben J. Mans; Lidia Chitimia-Dobler; Ronel Pienaar; Minique de Castro; Mehran Khan; Mashal M. Almutairi; Abdulaziz Alouffi; Abid Ali; Ala Tabor (Parasitology)
Two major families exist in ticks, the Argasidae and Ixodidae. The Argasidae comprise 2 sub-families, Argasinae and Ornithodorinae. The placement into subfamilies illuminate differences in morphological and molecular systematics and is important since it provides insight into evolutionary divergence within this family. It also identifies fundamental gaps in our understanding of argasid evolution that provide directions for future research. Molecular systematics based on mitochondrial genomics and 18S/28S ribosomal RNA confirmed the placement of various genera and subgenera into the Argasinae: Argas (including Argas and Persicargas), Navis, Ogadenus, Otobius lagophilus, Proknekalia, Secretargas and the Ornithodorinae: Alectorobius, Antricola (including Antricola and Parantricola), Carios, Chiropterargas, Nothoaspis, Ornithodoros (including Microargas, Ornamentum, Ornithodoros sensu strictu, Pavlovskyella), Otobius sensu strictu, Reticulinasus and Subparmatus. The position of Alveonasus remains controversial since traditional taxonomy placed it in the Ornithodorinae, while cladistic and limited molecular analysis placed it in the Argasinae. The current study aimed to resolve the systematic position of Alveonasus using mitochondrial genomic and 18S/28S ribosomal RNA systematics by sequencing the type species Alveonasus lahorensis from Pakistan. In addition, the mitochondrial genomes for Argas reflexus and Alectorobius kelleyi are reported from Germany and the USA, respectively. The systematic data unambiguously place Alveonasus in the Argasinae and also suggest that Alveonasus may be another paraphyletic genus.